Rating of amplitudes of high harmonics in determining feeder with single-phase ground fault - A. I. Fedotov; L. V. Akhmetvaleeva; R. S. Basyrov; G. V. Vagapov; E. A. Fedotov (Известия высших учебных заведений: Проблемы энергетики)
The aim of the paper is theoretical and experimental research of processes during the single-phase ground faults in electrical distribution grids of 10/06/35 kV with isolated neutral mode. The mathematical method of rationing is used for the analysis of the spectral composition of currents and voltages increasing the information content of the allocated higher harmonics of current and voltage. The paper show a comparison of the results of spectral analysis with and without taking into account the mathematical rationing obtained on the simulation model. Field experiments have demonstrated the effectiveness of using of the method of mathematical rationing of the higher harmonic components of current and voltage for various types of single-phase ground faults. The results of field experiments provided an opportunity of improving the methodology of yearling detection of single-phase ground faults in electric grids of 6-10-35 kV with an isolated mode of neutral. The conclusion of the research is the possibility of a significantly more accurate selection of the resonant frequencies of the spectrum of currents and voltages obtained by using of the method of mathematical rationing. The possibility of earlier and more precise localization of the feeder with ground fault is shown on the base more precise selection of the resonant frequency currents and voltages.